Adoption Of Artificial Intelligence In Women's Culinary Micro-Enterprises: The Role Of Social Capital And Gender Barriers - Putri Ervadhita R.; Muhammad Ahmi Husein (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study examined how women micro-entrepreneurs in the culinary sector in Surabaya, Indonesia understood, responded to, and prepared for the adoption of Artificial Intelligence (AI) in their business operations. A qualitative phenomenological design was employed, involving 15 purposively sampled women micro-entrepreneurs. Data were collected through semi-structured in-depth interviews and analysed using reflexive thematic analysis. Four themes emerged: (1) social capital and family support as facilitators of layered technology adoption; (2) institutional gaps in gender-responsive training ecosystems; (3) heterogeneous AI literacy ranging from no awareness to active use; and (4) multilayered gender-based barriers, including the novel ‘AI ease paradox’—a phenomenon in which the perceived ease of AI use inhibits the development of deeper AI literacy. The findings extend the TAM/UTAUT framework by integrating Social Capital Theory and a gender lens, offering theoretical and practical contributions for policymakers, training providers, and AI developers in the Southeast Asian micro-enterprise context.